Bandwidth in Joint Adjustment of Geodetic Networks Having Common Points - Öztan, Olcay; Kalkan, Yunus; Kizilsu, Zafer; Özerman, Ufuk (American Society of Civil Engineers (ASCE), 1994)
In this paper, a formula is presented for obtaining the bandwidth that would allow the inclusion of the normal equation coefficients differing from zero into the band, which are derived during the adjustment of several geodetic networks having common points. The given formula indicates that the process of combining the directions in the geodetic network, which considered as a contrary operation to the adjustment rules, increases the bandwidth. In the case of combining the directions without renumbering, in the model network consists of two networks having common points, it is determined that the bandwidth has increased around 55%. A method is also suggested for application of the numbering of network points in order to decrease the bandwidth as little as possible in the joint adjustment of connection and route networks of a motorway. It has been seen that it would be possible to obtain a result sufficiently close to the minimum bandwidth when using the method rapidly. The results obtained and the points t...